Pengaruh Jenis Latihan dan Usia terhadap Ketahanan Kardiorespirasi pada Atlet Sepak Bola - Agustanico Dwi Muryadi; Slamet Santoso; Sunjoyo; Muhammad Bagus Bimo Hartono (MAN Insan Cendekia Jambi, 2025)
This study aimed to examine the effects of different training methods and age groups on the cardiorespiratory endurance of soccer athletes. A quantitative experimental approach was employed using a 2×2×2 factorial design. The participants consisted of 32 football school athletes who were categorized based on training method, interval training and fartlek training, and age group, namely 12-year-old and 14-year-old athletes. Cardiorespiratory endurance was assessed using the Multistage Fitness Test (MFT) to determine VO₂max as an indicator of aerobic capacity. Data were collected through pretest and post-test measurements following a training program conducted over 16 sessions. Statistical analyses included tests of normality, homogeneity, analysis of variance (ANOVA), and Tukey HSD post hoc tests at a 0.05 significance level. The results indicated that interval training led to a greater improvement in cardiorespiratory endurance compared to fartlek training, with an increase of 6.27%. Moreover, athletes aged 14 years demonstrated higher improvements (5.43%) than those aged 12 years. A significant interaction between training method and age group was also identified. These findings highlight the importance of selecting appropriate training methods and adjusting training programs according to athletes’ age to enhance cardiorespiratory endurance in football.